Theoretical studies of plant-based peptides targeting human angiotensin converting enzyme-related carboxypeptidase - Oso, Babatunde; Olaoye, Ige; Aberuagba, Adepeju (Jordan Journal of Pharmaceutical Sciences, 2021)
Background The vulnerability of the lungs, intestine, heart and kidney to SARS-CoV-2 invasion is dependent on the high expression of angiotensin converting enzyme-related carboxypeptidase (ACE2) on the outer surface of the cells in these organs. This clear mode of interaction between SARS-CoV-2 spike proteins and ACE2 emphasizes the importance of ACE2 receptors in the spread of coronaviruses. This study investigated the binding potentials of some selected plant-based peptides (circulin A, kalata B1, Varv peptide E, palicourein, Vhl-1, griffithsin, cycloviolacin VY1) to ACE2 as a predictive approach in preventing SARS-CoV-2 invasion. Methods The peptides were retrieved from the antimicrobial peptide database and their respective physicochemical properties were predicted using ProtParam Tool. The binding mode and the binding free energies were computed through HawkDock servers while the structural flexibility and stability of the ACE2-peptide complexes were evaluated via the CABS-flex 2.0 server. Results It was observed that the binding scores for the peptides towards ACE2 showed good binding affinities with griffithsin having the best binding score through the Hawkdock rank while kalata B1 had the lowest binding score. The Molecular Mechanics/Generalized Born Surface Area analysis showed that the binding free energy ranges -39.99 and -3.96 kcal/mol with Vhl-1 having the highest free energy and palicourein having the least free energy. Conclusions The results of the study suggest that the selected plant-based peptides especially kalata B1, vhl-1, and cycloviolacin VY1 could be promising modulators of ACE2 and prevent the binding of the S1 domain of the SARS-CoV-2 S protein and consequent cellular entry of SARS-CoV-2.